MUTIVARIATE ANALYSIS IN STEM AMARANTH (Amaranthus tricolor) (Bangladesh Journal of Plant Breeding and Genetics, 2013)
The genetic divergence among 22 genotypes of stem amaranth was estimated using D² and Principal Component Analysis. The genotypes were grouped into four clusters. Cluster I, II, III and IV composed of two, four, seven and nine genotypes in succession. No relationship was found between divergence and geographic distribution of the genotypes. Maximum inter cluster distance (12.326) was observed between cluster I and III and it was minimum (3.526) between cluster I and II. The crosses between the genotypes of cluster I with that of cluster III and cluster II with cluster III would exhibit high heterosis and also likely to produce new recombinants with desired characters in stem amaranth. The yield contributing characters were leaves per plant, petiole length, stem diameter, leaf weight per plant and stem weight per plant. Leaf width, petiole length and 1000 seed weight showed maximum contribution to the total divergence. The results obtained by D² analysis were confirmed by Principal Component Analysis.DOI: http://dx.doi.org/10.3329/bjpbg.v26i1.19979